Application of Fuzzy Delphi Method in Exploring Facebook as a Tool for Writing Therapy Among Young Adults (Malaysian Online Journal of Educational Technology, 2014)
Social media sites including Facebook are increasingly accessed and integrated in the counselling and psychotherapy profession. As there is a universal escalation of mental and emotional health needs in today’s society especially among young adults, Facebook as a popular social networking site for Malaysian youths could be taken advantage as a platform for expressive writing. However, there is a significant deficiency in the available body of knowledge regarding Facebook as a potential online intervention medium. This study aimed at examining the consensus level of 22 experts in the field of counselling and psychology on the suitability of Facebook as a platform for writing therapy intervention in the Malaysian context using the Fuzzy Delphi Method. Findings identified contradictory views among the experts on the survey items, which indicated the inadequate understanding of the applicability of writing therapy via online-based mediums. As the Internet continues to proliferate throughout the world, the potential of Facebook as a medium for intervention should be further tapped into. This study would elicit increased awareness of the applicability of Facebook to help shape the future in the field of psychotherapy and counselling in Malaysia. A sample plan for an exploratory implementation study was established for future research use.